Meningiomas com características histológicas atípicas : estudo por análise histológica e clínico-cirúrgica - Marcos, Debora Salles [UNIFESP] (2017)
Meningiomas are tumors originating from arachnoid cells and constitute the most common intracranial tumors, comprising up to 36% of all primary intracranial neoplasms. They are classified by WHO as benign (grade I), atypical (grade II) or malignant/anaplastic (grade III). For the histological and prognostic definition of the lesion, it is often necessary to use immunohistochemical techniques, which solve most of the cases that require differential diagnosis. Objectives: To perform a histological review of cases of grade II and grade I atypical meningiomas with spontaneous necrosis, comparing to grade III; to evaluate the histological and immunohistochemical factors of patients prognosis, while correlating information in clinical-pathological scope with the clinical follow-up of the patients. Method: A review of 36 cases of benign meningiomas with spontaneous, atypical and anaplastic necrosis of patients treated at Hospitals São Paulo, Diadema and Pirajussara from 2001 to 2014. The samples were submitted to immunohistochemical examination with the following markers: p53 protein, Ki-67 cell proliferation factor and progesterone receptor. Results: The expression found for each marker confirmed the reports of most studies already performed in this field: greater expression in the progression of the several degrees of aggressiveness for p53 and Ki-67 and higher frequency of progesterone receptors in the lower degrees of aggressiveness. The group of grade I meningiomas with spontaneous necrosis demonstrated prognostic indexes that approximate those of the atypical meningiomas. Conclusion: Histological and especially immunohistochemical factors showed significant differences between the groups of grades I and III meningiomas. The study of prognostic markers in these tumors has been useful to corroborate the grades of histological meningioma. The group of grade I meningiomas with necrosis still requires more study and interaction of the cases, mainly with the follow-up of the patients.